(untitled) (Nexus International Journal of Science and Education, 2024)
This study extracted the experiences of elementary learners favorite pastime using the modern technologies specifically in Maa District, Davao City. There were eight (8) learners who participated in the study. This study made use of a phenomenological approachto extract the ideas from the informants. The face to face in-depth-interview was employed to gather information as regards to their respective experiences. Using the thematic analysis, the following themes emerged as it relates to the experiences of the participants: Addicted to online games, Reduced focus on learning activities and Used as source of information. The coping mechanisms of the elementary learners were: “No game at school” strategy and Use gadgets for online research only. The educational management insights were focused on two factors: Improve school policies on the use of gadgets or lap tops and No use of gadgets duringclass hours. Based on the fidigs of the study, the following recommendations were given: The elementary teachers may consider several strategies to gain the attention of the learners in their quest of knowledge through their hand-held gadgets. Constant reminders on the proper use of these gadgets may be a regular task of the classroom teachers to regain the attention of the learners and guide them on the proper use of search engines to search important information. The parents may be given proper information and guidelines on the use of hand-held gadgets of their children. Being aware of the importance of communication, these hand-held gadgets may be put into proper use as guided by their parents and classroom teachers. The learners may be directed well through the constant reminders of their class advisers and on the right time to use and not to use their cellular phones in and out of their classrooms.